Increased mortality and hospital readmission risk in patients with dementia and a history of cardiovascular disease: Results from a nationwide registry linkage study. (21st December 2018) - van de Vorst, Irene E.; Vaartjes, Ilonca; Bots, Michiel L.; Koek, Huiberdina L.
Abstract : Objective: To evaluate the impact of cardiovascular disease (CVD) on mortality and readmission risk in patients with dementia. Methods: Prospective hospital‐based cohort of 59 194 patients with dementia admitted to hospital or visiting a day‐clinic between 2000 and 2010. Patients were divided in those with and without a history of CVD (ie, previous admission for CVD; coronary heart disease, heart failure, stroke, atrial fibrillation, or other CVD). Absolute mortality risks (ARs), median survival times, and hazard ratios (adjusted for age, sex, and comorbidity) were calculated. Results: Three‐year ARs and HRs were higher, and survival times were shorter among patients visiting a day‐clinic with a history of CVD than in those without. The differences were less pronounced for inpatients. Readmission risk was further increased in the presence of CVD in both day clinic and inpatients. Conclusion: Clinicians need to be more aware of worse prognosis of the population with CVD and dementia.